Cigarette Smokers are Less Likely to Have Undetectable Viral Loads: Results From Four HIV Clinics. Issue 1 (February 2016) - Cropsey, Karen L.; Willig, James H.; Mugavero, Michael J.; Crane, Heidi M.; McCullumsmith, Cheryl; Lawrence, Sarah; Raper, James L.; Mathews, W. Christopher; Boswell, Stephen; Kitahata, Mari M.; Schumacher, Joseph E.; Saag, Michael S.; et al.
Abstract : Background: The prevalence of smoking among HIV-infected individuals is 2–3 times that of the general population, increasing the risk of smoking-related morbidity and mortality. We examined characteristics associated with smoking behavior among a large cohort of HIV-infected individuals in care in the United States. Methods: A convenience sample of 2952 HIV-infected patients in the Centers for AIDS Research (CFAR) Network of Integrated Clinical Systems (CNICS) was assessed during routine clinic visits and was included. Multinomial logistic regression was used to examine the relationship between smoking status, depression/panic symptoms, alcohol/substance use, and demographic and clinical characteristics. Results: Compared with never-smokers, current smokers were more likely to have moderate to severe depression (odds ratio [OR] 1.37), endorse current substance use (OR 14.09), and less likely to report low-risk alcohol use on the Alcohol Use Disorders Identification Test (AUDIT-C) (OR 0.73). Current smokers were less likely to have an undetectable viral load (OR 0.75), and more likely to have current substance abuse (OR 2.81) and moderate to severe depression (OR 1.50), relative to smokers who had quit smoking. Conclusions: HIV-infected smokers are less likely to have undetectable viral loads and frequently have psychosocial comorbidities including depression and substance abuse that impact antiretroviral therapy adherence and viral load suppression. To be effective, smoking-cessation interventions need to address the complex underlying concurrent risks in this population.